2022
DOI: 10.1101/2022.02.14.22269692
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuroimmune transcriptome changes in brains of psychiatric and neurological disorder patients

Abstract: Neuroinflammation has been implicated in multiple brain disorders but the extent and the magnitude of change in immune-related genes (IRGs) across distinct brain disorders has not been directly compared. We curated 1,275 IRGs and investigated their expression changes in 2,467 postmortem brains of controls and patients with six major brain disorders, including schizophrenia (SCZ), bipolar disorder (BD), autism spectrum disorder (ASD), major depressive disorder (MDD), Alzheimer's disease (AD), and Parkinson's di… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 112 publications
0
4
0
Order By: Relevance
“…Moreover, the same working group found associations between schizophrenia and genes with important roles in immunity, in line with observational and clinical studies highlighting the connections between immune and inflammatory processes in psychiatric disorders (Benros et al, 2012;Smyth and Lawrie, 2013;Kroken et al, 2018;Hughes and Ashwood, 2020). More recently, research on psychiatric and neurological disorders has increasingly pointed to the neuralimmune interface as potential source of disease markers, thereby enabling the identification of new neurobiological targets (Afridi et al, 2021;Chen et al, 2023).…”
Section: Introductionmentioning
confidence: 63%
“…Moreover, the same working group found associations between schizophrenia and genes with important roles in immunity, in line with observational and clinical studies highlighting the connections between immune and inflammatory processes in psychiatric disorders (Benros et al, 2012;Smyth and Lawrie, 2013;Kroken et al, 2018;Hughes and Ashwood, 2020). More recently, research on psychiatric and neurological disorders has increasingly pointed to the neuralimmune interface as potential source of disease markers, thereby enabling the identification of new neurobiological targets (Afridi et al, 2021;Chen et al, 2023).…”
Section: Introductionmentioning
confidence: 63%
“…Therefore, specific neuropathologies associated with AD and Parkinson's disease (PD), may be an initial trigger of the proinflammatory response which ultimately impacts on systemic functions and gut microbes. It is also noteworthy that the same study reported clustering of innate immune transcripts between autism spectrum disorder (ASD) and neurological disorders (AD, PD) rather than psychiatric disorders (bipolar disorder [BD], schizophrenia [SCZ], major depressive disorder [MDD]) (Chen et al, 2022). The grouping of ASD with neurological diseases is unexpected, given that it is considered to be a neurodevelopmental disorder.…”
Section: Brain Injury Inflammation and Neuropathologymentioning
confidence: 99%
“…A recent analysis of immune-related gene expression in post mortem brain samples from several neuropsychiatric disorders demonstrated neuroimmune dysregulation was more prominent in neurological disorders, particularly Alzheimer's disease (AD), than in psychiatric disorders (Chen et al, 2022). Therefore, specific neuropathologies associated with AD and Parkinson's disease (PD), may be an initial trigger of the proinflammatory response which ultimately impacts on systemic functions and gut microbes.…”
Section: Brain Injury Inflammation and Neuropathologymentioning
confidence: 99%
See 1 more Smart Citation